Sistem Pendukung Keputusan Penerimaan Staff Pengajar Menggunakan Simple Addictive Weighting Pada LPIA Dukuh Zamrud - Syahfitri, Intan Cahya; Solikin, Solikin (Journal of Students‘ Research in Computer Science, 2021)
Acceptance of teaching staff is an important process that aims to improve the productivity of a company's performance. The reception of teaching staff at the LPIA Hamlet Zamrud Bekasi still uses conventional methods so it requires a long time in the management process. Seeing this, it is necessary to have a computerized data management and decision making system for prospective teaching staff based on predetermined criteria namely micro teaching, teaching experience, recent education and age. In implementing a decision support system using the Simple Addictive Weighting (SAW) method, this method was chosen because in its calculation it can determine the weight values for each attribute, then proceed with the ranking process which will choose the best alternative from several alternatives based on the weights and criteria that have been set specify it. By using criteria to assist in the development and development of decision support systems for system development using the RAD (Rapid Application Development) method. Design and system analysis uses Unified Modeling Language (UML). By using the SAW method, the decision making for teaching staff acceptance becomes easier so that it speeds up the decision making process for teaching staff acceptance.